The Evolution of School Health and Nutrition in the Education Sector 2000–2015 in sub-Saharan Africa - Sarr, Bachir; Fernandes, Meena; Banham, Louise; Bundy, Donald; Gillespie, Amaya; McMahon, Brie; Peel, Francis; Tang, K. C.; Tembon, Andy; Drake, Lesley (Frontiers in Public Health, 2017)
Study objectives: To document the progression of school health and nutrition and its integration within the education sector in sub-Saharan African countries between 2000 and 2015. Background: School health and nutrition programs have contributed to “Education for All” objectives by helping ensure that children benefit from quality education and reach their educational potential. Methods: Analysis of Education Sector Plans in terms of the Focusing Resources on Effective School Health (FRESH) framework and the World Bank Systems Assessment of Better Education Results (SABER) School Health survey from a set of countries in sub-Saharan Africa. Results: Between 2000 and 2015, the presence and scope of school health and nutrition as reflected in the four FRESH pillars grew substantially in Education Sector Plans. Three of these pillars have large, upfront costs. The fourth pillar requires recurring annual budgetary allotments. Conclusion: Governments clearly recognize that evidence-based, contextually-designed school health and nutrition programmes can contribute to education sector goals. Moving into the post-2015 era, these programmes can also help draw the last 10 percent of children into school and enhance their readiness to learn.